The effect of US States’ environmental policies on their own carbon emissions - Kennedy, Colby. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
Reducing carbon emissions has been a longstanding goal of policy makers, who have implemented a variety of taxes, incentives, and mandates to achieve emissions reductions in line with their own goals as well as international climate agreements. In the United States, both command-and-control policies and market- based policies have been implemented in different combinations and with different design choices under different circumstances. Understanding the effect of these policies individually as well as the benefits of each approach generally is critical for states to design and implement effective climate policies. This thesis studies the effect of three of these policies; carbon markets, environmental review, and renewable portfolio standards together in order to both compare the effects of each policy as well as to better separate the effects of each policy from the total effect of all policies in the context of the United States. We find that carbon market schemes in the US are effective in accelerating the transition to a low carbon economy, while renewable portfolio standards and environmental review policies are not effective or may even be impairing the transition to a low carbon economy.
Keywords: Carbon dioxide mitigation -- Economic aspects.; Environmental policy -- Economic aspects.; Economic development -- Environmental aspects.; Environmental policy -- United States.